Scheduling for Machine Type Communications in LTE Systems - Bekele, Yared Zerihun; Choi, Young June (9th International Conference on Information and Communication Technology Convergence: ICT Convergence Powered by Smart Intelligence, ICTC 2018, 2018)
To accommodate the massive connectivity of Internet-of-Things (IoT) such as a smart meter application for cellular networks, 3GPP has standardized Machine Type Communication (MTC) and cellular IoT. The data transmission of such IoT exhibits a time-controlled and an event-driven feature which delivers short messages with low data rate but supports massive connectivity. In MTC and its advanced system including eMTC and 5G-NR, legacy data and IoT data share radio resource; thus, any existing scheduler can handle both types of data separately. In this paper, we prove that existing schedulers that favor instantaneous channel quality do not work effectively for IoT data. Based on this property, we suggest a modified First Maximum Expansion (m-FME) algorithm that removes channel feedback. Through simulation, we confirm that m-FME outperforms existing schedulers.
Keywords: 5G/LTE; Advanced systems; Cellular network; Channel feedbacks; Internet of Things (IOT); Machine type communications; Machinetype communication (MTC); Time-controlled; 5G/LTE; MTC; Scheduling